Inter-particle bonding mechanisms in biopolymer-hydrogel stabilized granular soils: A microscopic perspective - Lee, Sojeong; Chang, Ilhan (Geomechanics and Engineering, 2025)
Biopolymer-based soil treatment (BPST) enhances soil strength through biofilm matrix formation within soil voids. This study investigates the effects of biopolymer concentration, porosity, and soil packing conditions on biopolymer distribution and connectivity after dehydration. Laboratory experiments assessed the degree of biopolymer filling (DoBF), final condensed biopolymer concentration, and biopolymer film connectivity under simple cubic and rhombohedral packing conditions. The results show that higher initial biopolymer concentrations increase final biopolymer volume, though not proportionally due to threshold effects. Rhombohedral packing results in higher final condensed biopolymer concentrations than simple cubic packing, despite having lower DoBF values, while biopolymer connectivity peaks at an optimal porosity (n ≈ 0.35). Further analysis revealed a strong correlation between biopolymer matrix formation and soil mechanical properties, including uniaxial compressive strength (UCS), cohesion, and friction angle. UCS was found to decrease with increasing porosity, and a predictive model was developed using experimental data. The rhombohedral and simple cubic packing conditions respectively define the upper and lower bounds of the shear parameters. A back-calculation approach confirmed that DoBF provides the most accurate estimation of friction angle and UCS, reinforcing its importance as a key parameter in soil stabilization. These findings emphasize the need for optimized biopolymer concentration and soil structure adjustments to enhance reinforcement efficiency. The study offers valuable guidance for geotechnical applications, enabling the development of optimized biopolymer injection strategies that enhance mechanical performance and promote efficient material utilization.
Keywords: Biopolymer-based soil treatment; Friction angles; Geotechnical; Interparticle bonding; Matrix formation; Packing conditions; Particles bonding mechanism; Simple cubic packing; Soil treatments; Uniaxial compressive strength; biopolymer; biopolymer-based soil treatment (BPST); geotechnical engineering; Xanthan gum